Bimbingan Belajar: Membantu Anak-Anak Kurang Mampu Mencapai Prestasi Akademik - Azizah, Laelah; Mannahali, Misnah; Asri, Wahyu Kurniati; Angraeny, Femmy; Burhamzah, Rahmat (Program Studi Manajemen FEB UNM, 2024)
Learning guidance is an effective effort in improving academic achievement, especially for children from socio-economically disadvantaged backgrounds. This tutoring program is designed to provide more intensive attention to students' academic, social, and emotional development. The results of its implementation show a significant improvement in understanding of subject matter, increased self-confidence, and higher motivation to learn among the participants. Additionally, the tutoring program has contributed to strengthening the relationship between parents and children and has had a positive impact on the development of students' social skills. Through an empathetic approach and interactive methods, the tutoring program has helped students overcome learning barriers and build a positive attitude towards education. The long-term impact of this program includes increased opportunities for higher education and overall improvement in quality of life. Therefore, tutoring for underprivileged children not only improves their academic performance but also makes a significant contribution to character development and prepares them for the future.